Reinforcement and response rate interaction in multiple random-interval avoidance schedules - De Villiers, Peter A. (1972)
Two experiments were conducted to investigate the interaction between response rate and reinforcement frequency in multiple random-interval avoidance schedules. Responses cancelled delivery of shocks that could be scheduled at different random intervals in each component. When shock-frequency reduction was taken as the measure of reinforcement, the relationship between response rate and frequency of reinforcement was described by the same equations used by Herrnstein (1970) to describe responding with positive reinforcement.